Effect of inoculating mycorrhizal fungi and Rhizobium on broad bean (Vicia faba L.) growth at different phosphorus levels in calcareous soil. - Ahmed, Fryal Qadir; Fattah, Omar Ali (Sulaimani Journal for Pure and Applied Sciences, 2019)
The experiment was carried out, under plastic house at the college of Agricultural Engineering Sciences, University of Sulaimani, Bakrajo, during 2018-2019 to determine influence of inoculation with arbuscular mycorrhizal fungi (AMF) and Rhizobium leguminosarum at different phosphors levels (0, 40, 80, 120 and 160 kgPha-1) on broad bean (Vicia faba L.) growth and nutrient uptake. The experiment was performed in a factorial experiment with completed randomized design (CRD) in a silty clay soil, with three replications for each treatment. After ten weeks of growth, the plants were harvested to determine plant growth (root colonization, shoot dry weight, root dry weight, nodule number, and shoot nutrient content N, P, K, Fe and Mo The results showed that inoculated broad bean plants with mycorrhiza or the bacterium Rhizobium leguminosarum increased plant growth and nutrient uptake compared with non-inoculated plant. Inoculated soil with AMF increased root colonization, shoot dry weight, root dry weight, and nodule number the highest value was (65%, 15.09gpot-1, 7.72gpot-1 and 128.67 nodule pot-1) respectively and the highest value for shoot N, P, K, Fe and Mo nutrients were (15.68gkg-1, 4.38gkg-1, 17.72 gkg-1, 184.00µgg-1 and 0.83 µgg-1) respectively recorded at highest P level (160 kgPha-1). But when the soil inoculated with the Rhizobium leguminosarum, the effect was increased plant growth, (root colonization ,shoot dry weight, root dry weight and nodule number) The highest value was(26.67% , 15, 60gpot-1, 8.03gpot-1 and 191.33nodule pot-1 ) recorded at highest P level, and inoculation with R. leguminosarum was increased significantly shoot N, P, K, Fe and Mo contents, the highest value were (20.35gkg-1, 3.72 gkg-1,16.78 gkg-1, 175.33 µgg-1 and 0.80 µgg-1 )respectively recorded at highest P level (160 kgPha-1).
Keywords: Phosphorus; Arbuscular Mycorrhiza; Rhizobium leguminosarum; Broad bean Nutrient uptake